Answer:
y = 2 x minus 6
Step-by-step explanation:
(-6,-18) and (-1,-8)
Slope: (-8 - -18)/(-1 - -6)
10/5
2
y = 2x + c
-8 = 2(-1) + c
-8 = -2 + c
c = -6
y = 2x - 6
y = 2x - 4
Answer:
x > -6
Step-by-step explanation:
Move 6 to the other side:
0.5x > -3
x > -6
First we have to rewrite this function.Instead of :^3 sqrt (...) we can write : (...)^(1/3).
f ( x ) = ( 27 x - 81 ) ^(1/3) - 5 = ( 27 * ( x - 3 ) ) ^(1/3) - 5 = = 3 * ( x - 3 )^(1/3) - 5 And this makes it easy to graph a translation.The parent function is y = x^(1/3). The zero of this function is ( 0, 0 ).
Then it will be stretched vertically by a factor of 2 and translated: 3 units right and 5 units down.
Answer:
reduce 10 qauts of 50%
Step-by-step explanation:
I don’t not know the answer for this question sorry